Switched controller applied to functional electrical stimulation of lower limbs under fatigue conditions: A linear analysis - Nunes, W. R.B.M. [UNESP] (2019)
Individuals with spinal cord injury may improve lower limb mobility with neuromuscular electrical stimulation. Several studies propose closed-loop controller simulations, but few of them know the experimental behavior. From experimental results, we observe that the control signal is uncertain for an operating point, because of plant uncertainties. An experimental setup in order to identify the linear model containing polytopic uncertainties is presented in this paper. In addition, a controller pσ, ξ(t) that compensates uncertain control signal through an adequate switching law was designed. Results obtained from open-loop control p(t) = p0 and switched controllers p(σ)(t) and p(σ, ξ)(t) are compared. These results indicate that switched controller p(σ, ξ)(t) minimizes the uncertain control signal and returns the smallest time derivative value of the Lyapunov function, consequently minimizing the angular position error in electrically stimulated lower limbs under fatigue conditions.